The effectiveness of marketing strategy used by Takaful Nasional Sdn. Bhd., Kuching in marketing their products / Siti Faridah Hanum Zaidel - Hj Zaidel, Siti Faridah Hanum (1999)
In efforts toward sustaining the nation’s robust economy and to assimilate Islamic values, the Malaysian government has strived to implement Islamic Financial System in tandem with the conventional financial structure. The Islamic Financial System which is based on syariah laws covers institutions like Al Bank Alla’ Ribawi (Free Interest Banking), Takaful (Insurance), Ar Rahn (Pawn Broking) and Islamic shares transaction have gained the support of Muslims and non Muslims alike. Insya Allah, the Islamic Muamalah will be the business culture of future.